2017
DOI: 10.1186/s12885-017-3698-2
|View full text |Cite
|
Sign up to set email alerts
|

Skip metastasis in papillary thyroid carcinoma is difficult to predict in clinical practice

Abstract: BackgroundCervical lymph node metastases are very common in papillary thyroid cancer (PTC), and typically spread in a predictable stepwise fashion in clinical practice. However, lateral lymph node metastasis (LLNM) without central lymph node metastasis (CLNM) as skip metastasis is not rare in PTC. The aim of this study was to investigate the incidence, risk factors and pattern of skip metastasis in PTC.MethodsA total of 271 patients with PTC and suspicious LLN diagnosed by pre-operation examinations who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
50
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 43 publications
10
50
3
Order By: Relevance
“…4,9,10 The incidence rate of skip metastasis ranges from 6.8% to 27.8% in PTC with LLNM. 15,20 In our study, skip metastasis was present in 62 out of 256 patients with LLNM (24.2%), which is a higher rate than in most other studies. The reason may be that all patients enrolled had PTMC, which is considered a risk factor for skip metastasis.…”
Section: Discussioncontrasting
confidence: 49%
“…4,9,10 The incidence rate of skip metastasis ranges from 6.8% to 27.8% in PTC with LLNM. 15,20 In our study, skip metastasis was present in 62 out of 256 patients with LLNM (24.2%), which is a higher rate than in most other studies. The reason may be that all patients enrolled had PTMC, which is considered a risk factor for skip metastasis.…”
Section: Discussioncontrasting
confidence: 49%
“…Whereas, without central metastases, the lateral LNM can also occur in PTC patients, known as skip metastasis. 27 This study found that skip metastasis was more common in patients with SLNM than in patients with MLNM, supported by previous reports. 26,31 ROC curve analysis determined that 1.15 cm was an optimal tumor size cutoff for predicting MLNM.…”
Section: Discussionsupporting
confidence: 90%
“…LNM is a risk factor for recurrence in PTC. 27,28 Lymph node dissection can significantly improve prognosis, so lymph nodes should be carefully evaluated before surgery. At present, there is still no clear suggestion on the scope of lateral neck dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we noted that female sex, advanced age, inferior lobe of the thyroid, MTD < 1 cm, and nodular goiter were positively associated with the incidence of skip metastases, while capsular infiltration was negatively associated with skip metastases in multivariate analysis. Similar to these results, Jin et al and Nie et al also found that small TCs (MTD < 1 cm) are more likely to have skip metastases (24,25).…”
Section: Skip Metastasissupporting
confidence: 71%